Between home and headquarters : How the pandemic transformed where people work and why it matters? - Pomochshikova, Mariya; Hořáková, Marie; Legnerová, Kateřina, 1965-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis discusses the changing trends in remote and hybrid work after the COVID-19 pandemic. The research in the practical side is focused on the experience of employees from the finance department in the Prague branch of an international healthcare company to provide suggestions on how to engage them more with in-office work without causing resistance or dissatisfaction. In the study is used a combination of theoretical analysis through the frameworks such as the Job Demands–Resources Model, Boundary Theory, Sociotechnical Systems Theory, and Results-Only Work Environment, and qualitative research based on employee interview answers. The study offers practical recommendations for adjusting hybrid work practices for specific department needs, increasing the value of office presence, and supporting employee well-being. The insights of the research suggest broader discussions on the future of work and remark that successful hybrid models require investment in both technological and cultural infrastructures.
Vedoucí práce: Marie Hořáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses